2014
DOI: 10.1186/1744-9081-10-23
|View full text |Cite
|
Sign up to set email alerts
|

A common haplotype of KIAA0319 contributes to the phonological awareness skill in Chinese children

Abstract: BackgroundPrevious studies have shown that KIAA0319 is a candidate gene for dyslexia in western populations. In view of the different languages used in Caucasian and Chinese populations, the aim of the present study was to investigate whether there is also an association of KIAA0319 in Chinese children with dyslexia and/or to the language-related cognitive skills.Method and resultsA total of twenty six single nucleotide polymorphisms (SNPs) were genotyped from three hundred and ninety three individuals from 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…rs3212236 located at 5’ was the most significant marker associated with word choice test (OC-choice), orthographic coding using irregular words (OC-irreg), single-word reading ability (READ) and spelling ability (SPELL) in the Oxford sample. Our group has also confirmed that a common haplotype of KIAA0319 contributes to phonological awareness skill in Chinese children [20]. Recently it has also been reported that brainstem responses as characterized by a reduction in neural discrimination abilities are associated with a higher number of risk alleles of KIAA0319 while no significant association has been found with DCDC2 (rs807724, rs1087266, rs807701, rs793842, rs1091047, rs6922023) and performance in reading and writing [21].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…rs3212236 located at 5’ was the most significant marker associated with word choice test (OC-choice), orthographic coding using irregular words (OC-irreg), single-word reading ability (READ) and spelling ability (SPELL) in the Oxford sample. Our group has also confirmed that a common haplotype of KIAA0319 contributes to phonological awareness skill in Chinese children [20]. Recently it has also been reported that brainstem responses as characterized by a reduction in neural discrimination abilities are associated with a higher number of risk alleles of KIAA0319 while no significant association has been found with DCDC2 (rs807724, rs1087266, rs807701, rs793842, rs1091047, rs6922023) and performance in reading and writing [21].…”
Section: Introductionsupporting
confidence: 77%
“…The significant haplotype rs2760157-rs807507 of KIAA0319 found in our previous study [20] was used for testing gene-gene interaction with DCDC2 . SNP-haplotype testing between rs2760157-rs807507 and each SNP of DCDC2 studied was evaluated for DD as well as for each reading related trait.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, initial evidence about associations between DD-candidate risk loci and genes and PA, RAP, RAN, attention and visual motion processing, have been provided. Following early observations of familial aggregation of phonological disorders (Lewis et al 1989), PA showed substantial heritability (Plomin & Kovas 2005), was consistently linked to DD-related susceptibility loci (Fisher et al 2002;Gayan et al 1999;Grigorenko et al 1997Grigorenko et al , 2003Wigg et al 2004;Willcutt et al 2002), and was associated with DYX1C1 and KIAA0319 (Lim et al 2014;Venkatesh et al 2014). The heritability of auditory processing in healthy populations was found to be high (Brewer et al 2016) and molecular genetics studies reported significant association with markers located on chromosomes 4 12 (Addis et al 2010).…”
mentioning
confidence: 95%
“…Similarly, even if some noteworthy genetic variants in KIAA0319 have been identified in both American and UK samples with DD (Cope et al 2005;Francks et al 2004;Harold et al 2006), the significant associations were not confirmed in independent American and Canadian samples (Brkanac et al 2007;Couto et al 2010). Similarly, a haplotype composed by three single-nucleotide polymorphisms (SNPs) spanning TTRAP, THEM2 and KIAA0319 has been shown to be associated with reading, spelling, orthographic and phonological skills in reading impaired families (Dennis et al 2009;Francks et al 2004), as well as in general population samples (Luciano et al 2007;Paracchini et al 2008), although negative findings have been reported (Cope et al 2005;Lim et al 2014).…”
mentioning
confidence: 99%
“…(Kaplan et al 2002), who found a microsatellite marker residing in KIAA0319 according to linkage studies. Then, dyslexia-KIAA0319 association studies are conducted in US (Francks et al 2004), UK (Harold et al 2006;Cope et al 2005), German (Ludwig et al 2008), Canadian(Couto et al 2010;Elbert et al 2011), Indian (Venkatesh et al 2011;Venkatesh et al 2013) and Chinese (Lim et al 2014;Sun et al 2014) population, suggesting several risk SNPs are associated with reading disability, such as rs4504469, rs6935076 and rs2038137. However, the results are not 3 always consistent since the difference of genetic and linguistic between ethnic groups.…”
Section: Introductionmentioning
confidence: 99%